Faktor-Faktor Yang Memengaruhi Penggunaan Lahan Pertanian Oleh Petani Pada Daerah Rawan Longsor Di Kecamatan Kejajar Kabupaten Wonosobo - Agastyan Akbar Syahputra Nugraha; Sri Rahayu (Jurusan Perencanaan Wilayah dan Kota, 2018)
Kejajar District is one of the districts included in the category of high landslide hazard at Wonosobo Regency. There are a few factors that may cause the hazard besides the topography condition, which is the high conversion of forestland to horticultural farming such as potato in particular. The decrease in forest vegetation, which has a strong root grip in highlands with steep slopes and its function as the water absorption region will accelerate the soil erosion. The aim of this study is to observe the factors affecting the horticultural land use by farmers in landslide prone areas with a quantitative method that consists of spatial analysis, descriptive statistic, and crosstab analysis. Based on the result of the study using the non-probability sampling, the result showed that the factors affecting horticultural land use were economic and socio-cultural factors. The length of time for horticultural farming business in the region with a time span of > 20 years, indicated that horticultural farming business was not only for consumption or potential exploitation of the natural characteristics. Yet, there was a beneficial factor from the economic side that brought the local communities to make use of their horticultural land for business. As time goes by, it eventually became a cultural order to the locals for making the horticultural land as business. The local government has made various conservative efforts, however reinforcement is needed from certain sides. Considering the planning and paradigm change are long term process, accordingly reinforcement is required not only from the technical side, but also from the non-technical side by collaboration and participative planning.